Developing Cognitive English Test on Recount Text Material - Nana Erna (SELTICS, 2020)
This study is development research. The purpose of the study is to develop a cognitive test that is valid and reliable, with a test that has the level of difficulty, differentiator, and effectiveness of distracter on the recount text material for the first semester students of the English Education Department at Sawerigading University of Makassar. The desired product of the study is a valid and reliable cognitive test that has the level of difficulty, differentiator, and effectiveness of distracter. The development process of the product employed formative research. The validity of the data obtained was analyzed systematically and categorized based on the set standard. The reliability was calculated by employing the ITEMAN program; whereas, the level of difficulty, differentiator, and distracter was analyzed by employing ANATES version 4 analysis. The trial was conducted at Sawerigading University of Makassar. The result obtained from the trial was a cognitive test with 23 questions in multiple-choice test out of 25 questions made in the first prototype which was valid and reliable. The test has the level of difficulty in the category of easy by 26%, medium by 52%, and difficult by 22%. The differentiator in all questions which consisted of 23 questions was at the range of 0.40. It has 0.1 categorized as good. The effectiveness of the distracter was 87% or 20 items with well-functioned distracter.